2018
DOI: 10.1136/bmjoq-2017-000167
|View full text |Cite
|
Sign up to set email alerts
|

Reducing the number of invalid surgical consents in the day surgery unit

Abstract: AimTo reduce the number of invalid surgical consents in the Singapore National Eye Centre Day Surgery Unit over a period of 6 months.MethodologyA multidisciplinary team involving doctors, nurses, day surgery unit, operating theatre, listing and clinical audit staff looked into the listing process and the root causes of the high number of invalid consents. A Pareto chart detailing the top causes of invalid consents was drawn, and with a prioritisation matrix, feasible yet effective changes were identified and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 5 publications
0
10
0
4
Order By: Relevance
“…Commonly for acute trauma admissions, this consenting process is performed by the clerking doctor to prepare the patient for an imminent operation. However often the clerking doctor may not be the surgeon performing the procedure and can be a relatively junior grade who is working under significant time or work pressure (4). These pressures have been noted to result in poor documentation and missed elements of admission notes (5) which can render important documentation such as consent forms substandard or even invalid (4).…”
Section: Introductionmentioning
confidence: 99%
“…Commonly for acute trauma admissions, this consenting process is performed by the clerking doctor to prepare the patient for an imminent operation. However often the clerking doctor may not be the surgeon performing the procedure and can be a relatively junior grade who is working under significant time or work pressure (4). These pressures have been noted to result in poor documentation and missed elements of admission notes (5) which can render important documentation such as consent forms substandard or even invalid (4).…”
Section: Introductionmentioning
confidence: 99%
“…However often the clerking doctor may not be the surgeon performing the procedure and can be a junior grade physician who is working under signi cant time or work pressure (4). These pressures have been noted to result in poor documentation and missed elements of admission notes (5) which can render important documentation such as consent forms substandard or even invalid (4).…”
Section: Introductionmentioning
confidence: 99%
“…Previous reviews of litigation relating to informed consent in the United States found errors in recording the risks of a procedure accounted for up to 70% of complaints alone (16). Furthermore, if consent documentation is of poor enough quality to be rendered entirely invalid, this can delay the operative pathway, potentially resulting in cancellation of procedures (4). In a time-critical situation such as hip fractures, these unnecessary delays can therefore signi cantly negatively impact patient care and outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Commonly for acute trauma admissions, this consenting process is performed by the clerking doctor to prepare the patient for an imminent operation. However often the clerking doctor may not be the surgeon performing the procedure and can be a junior grade physician who is working under significant time or work pressure [4]. These pressures have been noted to result in poor documentation and missed elements of admission notes [5] which can render important documentation such as consent forms substandard or even invalid [4].…”
Section: Introductionmentioning
confidence: 99%
“…Previous reviews of litigation relating to informed consent in the United States found errors in recording the risks of a procedure accounted for up to 70% of complaints alone [16]. Furthermore, if consent documentation is of poor enough quality to be rendered entirely invalid, this can delay the operative pathway, potentially resulting in cancellation of procedures [4]. In a time-critical situation such as hip fractures, these unnecessary delays can therefore significantly negatively impact patient care and outcomes.…”
Section: Introductionmentioning
confidence: 99%